(untitled) (International Seven Journal of Multidisciplinary, 2023)
The text addresses the mathematical knowledge present in the sociocultural activities of naval carpenters in the Tocantina Amazon region, state of Pará. It seeks to understand how this knowledge is acquired and applied in the construction of vessels and what relationships they have with school mathematics. Using an ethnomathematical approach, the work is theoretically based on authors such as: D’Ambrósio (2022); Knijnik (2004); Lucena and Fossa (2000); Pantoja (2015), Mendes and Farias (2014), among others. The work also highlights the geography and histories of the research site and the Amazonian-riverine peoples. Data were collected through observation and interviews with naval carpenters, holders of unique and valuable knowledge for the research. The results indicate that the carpenters have diverse knowledge about their culture, profession and the place where they live, acquired empirically over time, through experiences, mistakes and successes. The more experienced carpenters have a greater knowledge load, due to the contact and prolonged experience with the profession. By analyzing the mathematical knowledge involved in naval carpentry, the study shows applications of mathematical concepts in the field of Geometry, Algebra and Arithmetic, used empirically and transmitted to apprentices over the years. This knowledge is fundamental for the construction of stable, safe and quality vessels, and its transmission is essential for the continuity of this sociocultural practice.